2014
DOI: 10.3390/molecules19079114
|View full text |Cite
|
Sign up to set email alerts
|

Red Card for Pathogens: Phytoalexins in Sorghum and Maize

Abstract: Abstract:Cereal crop plants such as maize and sorghum are constantly being attacked by a great variety of pathogens that cause large economic losses. Plants protect themselves against pathogens by synthesizing antimicrobial compounds, which include phytoalexins. In this review we summarize the current knowledge on phytoalexins produced by sorghum (luteolinidin, apigeninidin) and maize (zealexin, kauralexin, DIMBOA and HDMBOA). For these molecules, we highlight biosynthetic pathways, known intermediates, propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 102 publications
(158 reference statements)
0
28
0
Order By: Relevance
“…Specialized herbivores may detoxify the aglycones [67][68][69] and even use them for their own benefit [33]. The best known of the BXs is DIMBOA (2,4-dihydroxy-7-methoxy-1,4-benzoxazin-3-one), which has been implicated in resistance against insect pests, as well as a number of pathogens [70]. The concentrations of BXs are typically higher in younger plants [71], and can be released in the rhizosphere [72].…”
Section: Discussionmentioning
confidence: 99%
“…Specialized herbivores may detoxify the aglycones [67][68][69] and even use them for their own benefit [33]. The best known of the BXs is DIMBOA (2,4-dihydroxy-7-methoxy-1,4-benzoxazin-3-one), which has been implicated in resistance against insect pests, as well as a number of pathogens [70]. The concentrations of BXs are typically higher in younger plants [71], and can be released in the rhizosphere [72].…”
Section: Discussionmentioning
confidence: 99%
“…Plants can enhance the rhizosphere environment (e.g., Peters et al, 1986;Besserer et al, 2006;Neal et al, 2012;Poloni & Schirawski, 2014), in order to attract soil microbes that can enhance plant growth by providing soluble inorganic nutrients and producing growth-promoting factors (Vanrhijn & Vanderleyden, 1995;Arshad & Frankenberger, 1998;Compant et al, 2005;Weisskopf et al, 2005;Bulgarelli et al, 2013). As for aboveground parts of plant system, we can, therefore, speculate that mutualistic interactions favoring plant vigor could also indirectly enhance the production of root exudates, including root-derived VOCs released after herbivore damage, and thus attracting more herbivore natural enemies.…”
Section: Soil Microbes Increase Plant Vigormentioning
confidence: 99%
“…Plant-microbe interactions involve a series of exchange of chemicals for signal perception, transduction, and metabolic responses. During pathogen infection, plant cells detect pathogen-associated molecular patterns (PAMPs), which lead to the production of specialized metabolites such as phytoalexins to combat the pathogen invasion ( Lin et al, 2014 ; Poloni and Schirawski, 2014 ; Arbona and Gomez-Cadenas, 2016 ). Past studies have also demonstrated that reprograming of the primary metabolic pathways contributes to the plant defense against pathogens.…”
Section: Introductionmentioning
confidence: 99%